1998
DOI: 10.1111/j.1559-1816.1998.tb01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal Theories of Hunger and Eating1

Abstract: Recent research on hunger and eating has shown that (a) among individuals with adlibitum access to food, hunger and eating are not regulated by deviations in the body's energy resources from set‐points, and (b) it is healthier for people to consume their daily caloric intake as several small snacks than as 3 large meals. People's beliefs about hunger and eating were assessed in 2 questionnaire studies. In Study 1, a large sample of undergraduates was surveyed; in Study 2, dietetics students, nursing students, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…On the other hand, the physiological state of the organism (e.g., hunger; Rolls, 2012 ) promotes or inhibits food research and consumption ( Small et al, 2001 ; Albrecht et al, 2009 ; Fernandez et al, 2013 ). Another extremely important aspect is represented by the cognitive and motivational factors of the individual ( Assanand et al, 1998 ), among which the tendency to avoid foods never encountered before (known as food neophobia; Pliner and Hobden, 1992 ) is receiving increased attention. The rationale behind this is the existence of a strong connection between new food avoidance with the successive development of unhealthy eating habits (e.g., assuming too much fats or sugars), that can have serious negative consequences on diet balancing or on body weight (e.g., obesity; Capiola and Raudenbush, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the physiological state of the organism (e.g., hunger; Rolls, 2012 ) promotes or inhibits food research and consumption ( Small et al, 2001 ; Albrecht et al, 2009 ; Fernandez et al, 2013 ). Another extremely important aspect is represented by the cognitive and motivational factors of the individual ( Assanand et al, 1998 ), among which the tendency to avoid foods never encountered before (known as food neophobia; Pliner and Hobden, 1992 ) is receiving increased attention. The rationale behind this is the existence of a strong connection between new food avoidance with the successive development of unhealthy eating habits (e.g., assuming too much fats or sugars), that can have serious negative consequences on diet balancing or on body weight (e.g., obesity; Capiola and Raudenbush, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous failures to confirm the major predictions of this set-point theory (see, e.g., Brandes, 1977;Friedman, Emmerich, & Gil, 1980;Smith, Gibbs, Strohmayer, & Stokes, 1972; W. H. Wilson & Heller, 1975) and the proposal of more defensible theoretical alternatives (see, e.g., Toates, 1981;Weingarten, 1985;Wirtshafter & Davis, 1977;Woods, 1991), set-point theory continues to dominate the thinking about hunger and eating of most laypersons, psychologists, and other health professionals. Indeed, in a recent survey of dietitians, nurses, doctors, and senior-year psychology students, Assanand, Pinel, and Lehman (1998) found that almost all believed that deviations from energy set points were the primary source of their motivation to eat. The fact that many of the important developments in the study of the regulation of hunger and eating do not seem to have influenced the set-point thinking of many psychologists was the major impetus for this article.…”
mentioning
confidence: 99%
“…To assess beliefs about healthy meal and snack patterns, two questions from the Personal Theories of Hunger and Eating Questionnaire (PTHE) (Assanand, 1996) were included. Participants were asked to respond to the questions "Three meals eaten at three different times during the day is…?"…”
Section: Beliefs About Healthy Meal and Snack Patternsmentioning
confidence: 99%
“…Another common belief is that consuming three meals throughout the day is healthy (Assanand, 1996). Again, the evidence supporting this claim is inconclusive.…”
Section: Introductionmentioning
confidence: 99%